Applicability of QbD-assisted Analytical Method for Simultaneous Detection of Tetrahydrocurcumin and Folic Acid in Developed Nanostructured Lipid Carriers - Kumari, Parina; Beg, Sarwar; Singh, Kamalinder K.; Kakkar, Vandita (Current Analytical Chemistry, 2024)
Aims: Applicability of QbD-assisted analytical method for simultaneous detection of tetrahydrocurcumin and folic acid in developed nanostructured lipid carriers. Background: Diabetic foot ulcer (DFU) is a multifactorial disorder that involves chronic inflammation, oxidative stress and neuropathy. Current treatment therapies involving the use of growth factors and skin substitutes being costly, are out of reach for the majority of patients. The present research explored the usefulness of a combination of tetrahydrocurcumin and folic acid-loaded nanostructured lipidic carriers in DFU. Objectives: To develop and validate a QbD-assisted method for simultaneous analysis of tetrahydrocurcumin (THC) and folic acid (FA). Applicability of the above method to determine total drug content (TDC) and entrapment efficiency (EE) of nanostructured lipid carriers (NLCs) loaded with THC and FA. Methods: A high-performance liquid chromatographic (HPLC) method was developed, optimized and validated using Box-Behnken design for improved method performance. Chromatographic separation was conducted on a Supelco 250 x 4.6 mm (5 μm) column with optimized mobile phase composition containing tetrahydrofuran: citric acid buffer pH 3.5 (50:50) at a flow rate of 0.4 mL.min-1 and diode array detection between 210 and 360 nm. Results: The method developed in a concentration range of 1 to 100 μg.mL-1 was found to be linear (R2 0.999, p≤0.001), accurate (99.10-101.70%) and precise with high recovery values in intra and inter-day results. The system adaptability and robustness evaluation revealed that the percent recovery ranged from 96.90 to 102.80%, and the percent relative standard deviation (%RSD) values were less than 2%. Moreover, the method was further applied for the determination of TDC (86±6% and 96±8%) and drug EE (81±21% and 73±13%) for THC and FA, respectively. Conclusion: The investigation indicated the applicability of the developed and validated method for the estimation of THC and FA in the developed nanostructured lipidic carriers.
Keywords: validation